Opercular syndrome: Case report - Torres-Ramírez, Luis (2020)
We present a patient with an opercular syndrome, with bilateral pseudobulbar symptoms and signs; most cases present involvement of both cerebral hemispheres, our patient had unilateral involvement. Clinical Case: A 65-year-old man, righthanded, with hypertension history, referred to a disease period of one year and one month of evolution, characterized by sudden monoparesis in the right upper limb, facial asymmetry, anarthria with bilateral pseudobulbar involvement. Magnetic resonance imaging showed ischemic lesion of the left opercular area. Discussion: The opercular or biopercular syndrome, also known as Foix-Chavany-Marie syndrome, is a rare entity characterized by involvement of the bilateral cerebral opercular area, which compromises the cortico-bulbar/protuberancial pathway. An important feature is the presence of the automatic-voluntary motor dissociation and the most frequent etiology in adults is ischemic, as in our case. The reason why a single lesion can produce bilateral pseudobulbar involvement is unknown, it is postulated a predominance of the protuberancial/bulbar cortical beam of the dominant hemisphere. In the published cases the prognosis is not favorable from the point of view of the language, but in our patient there was improvement of the anartria, swallowing, mastication and muscular strength, he received physical therapy with good evolution.